2011
DOI: 10.1038/ismej.2011.155
|View full text |Cite
|
Sign up to set email alerts
|

Geographically structured host specificity is caused by the range expansions and host shifts of a symbiotic fungus

Abstract: The inability to associate with local species may constrain the spread of mutualists arriving to new habitats, but the fates of introduced, microbial mutualists are largely unknown. The deadly poisonous ectomycorrhizal fungus Amanita phalloides (the death cap) is native to Europe and introduced to the East and West Coasts of North America. By cataloging host associations across the two continents, we record dramatic changes in specificity among the three ranges. On the East Coast, where the fungus is restricte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
36
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 53 publications
(65 reference statements)
0
36
0
Order By: Relevance
“…These results may indicate that many EM fungi have evolved compatibility to a wide range of co-occurring host lineages, such as Pinaceae, Fagaceae and Betulaceae that share overlapping geographic ranges (Bahram et al, 2013). Several studies also have suggested that host shifts among EM fungi prevail when preferable hosts are absent within a community (Trocha et al, 2012;Wolfe and Pringle, 2012;Bahram et al, 2013;Murata et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…These results may indicate that many EM fungi have evolved compatibility to a wide range of co-occurring host lineages, such as Pinaceae, Fagaceae and Betulaceae that share overlapping geographic ranges (Bahram et al, 2013). Several studies also have suggested that host shifts among EM fungi prevail when preferable hosts are absent within a community (Trocha et al, 2012;Wolfe and Pringle, 2012;Bahram et al, 2013;Murata et al, 2013).…”
Section: Discussionmentioning
confidence: 93%
“…Changes in spatial distributions of ECM fungi could be constrained, if there is a level of specificity between fungus and host and/or if the distribution of the host is limiting (Vellinga et al 2009). Meanwhile, there is evidence that some ECM species can associate with novel hosts, facilitating range expansion and invasion into new habitats (Wolfe and Pringle 2012). Meanwhile, there is evidence that some ECM species can associate with novel hosts, facilitating range expansion and invasion into new habitats (Wolfe and Pringle 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Saprotrophs may also be constrained by host distributions (Heilmann-Clausen et al 2016). Meanwhile, there is evidence that some ECM species can associate with novel hosts, facilitating range expansion and invasion into new habitats (Wolfe and Pringle 2012). Range expansions may lead on to fungal species becoming invasive (Kauserud et al 2007, Gladieux et al 2015.…”
Section: Introductionmentioning
confidence: 99%
“…However, if the two taxa specialized on local genetic strains, then we would find some degree of congruence among clades even at neutral loci. The incongruence indicates a lack of discrimination by the fungus for specific genetic strains of the photobiont as long as it is the right species, which would allow the lichen to associate with a locally adapted photobiont genetic strain and thus persist even when the fungus disperses to new environmental conditions (Romeike et al ., ; Piercey‐Normore, ; Wolfe & Pringle, ; Werth & Sork, ). Across environments, it would be beneficial to switch to a different genotype of alga (Piercey‐Normore, ).…”
Section: Discussionmentioning
confidence: 99%
“…Across environments, it would be beneficial to switch to a different genotype of alga (Piercey-Normore, 2006). Thus, these non-specific associations among haplotypes may promote novel combinations of fungi and algae and create the opportunity for adaptation to new conditions (Wornik & Grube, 2010;Wolfe & Pringle, 2011). Following the initial contacts and establishment, site-specific selective forces would retain the successful thalli and remove unfit symbiotic combinations (Yahr et al, 2006).…”
Section: High Clade-level Specificity Of the Lichen-forming Fungusmentioning
confidence: 99%